Some Thoughts on Cartographic Production Systems for Nautical Charting - Furness, Ronald A.; Halls, Ian W. (The International Hydrographic Review, 2015)
In this paper we discuss the Australian Hydrographic Branch’s experience with computer-based cartographic production since the early 1970’s and outline the current practices adopted by the Australian Hydrographic Office. We attempt to generalise the experience and, with one eye on the potentially extensive development of digital data acquisition systems (both sea- and air-bome) and the other on the likely demands of electronic charting graphics and the consequent need for change in hydrographic information management practices, we suggest some strategies for future hydrographic office procurement of cartographic production systems for nautical charting. Given the limited hydrographic market place in each hydrographic nation, including (relatively) even the largest nations, it is unlikely that the ideal solutions will become readily available from the market-place, despite the optimism of many land and geographic information systems vendors that their products cater for all graphics output requirements. Consequently a heavy development burden will fall on individual hydrographic offices unless international specification can transcend and complement particular governments’ procurement policies.